Diabetic status and grade of nonalcoholic fatty liver disease are associated with lower baroreceptor sensitivity in patients with nonalcoholic fatty liver disease. Issue 8 (August 2017) - Singh, Akanksha; Kumar, Mavidi S.; Jaryal, Ashok K.; Ranjan, Piyush; Deepak, Kishore K.; Sharma, Sanjay; Lakshmy, Ramakrishnan; Pandey, Ravindra M.; Vikram, Naval K.
Abstract : Objectives: Baroreceptor sensitivity (BRS), a functional consequence of vascular stiffness, may be affected by the presence of diabetes mellitus (DM) and nonalcoholic fatty liver disease (NAFLD). The present study was designed to assess the effect of diabetic status and NAFLD grade on the BRS in patients with NAFLD. Methods: Seventy-five individuals (25 NAFLD without DM, 25 NAFLD with DM and 25 controls) were recruited for the study who underwent anthropometric and body composition analysis along with estimation of plasma glucose, serum insulin and serum lipids. BRS and blood pressure variability (BPV) analysis was carried out in both time and frequency domains. Carotid–radial and carotid–dorsalis pedis artery pulse wave velocity, and radial artery augmentation index were computed as measures of arterial stiffness. Results: BRS was found to be lower in the NAFLD with DM group as well those with grade II NAFLD compared with the controls. Correlation analysis showed a negative correlation of BRS with postprandial blood glucose level ( r =−0.39) and BMI ( r =−0.467). The diabetic status and grade of NAFLD were associated independently with a decrease in BRS as well as the low-frequency component of diastolic BPV. The augmentation index and carotid–distal pulse wave velocity were higher in the NAFLD with DM group compared with controls. Conclusion: Both the diabetic status and grade of NAFLD were shown to have an independent effect on the decrease in the BRS with a consequent effect on BPV, with a greater influence of diabetic status rather than NAFLD grade on arterial stiffness.